Birth Weight, Body Silhouette Over the Life Course, and Incident Diabetes in 91,453 Middle-Aged Women From the French Etude Epidemiologique de Femmes de la Mutuelle Générale de l'Education Nationale (E3N) Cohort - de Lauzon-Guillain, Blandine (American Diabetes Association, 2010)
OBJECTIVE: Obesity and increases in body weight in adults are considered to be among the most important risk factors for type 2 diabetes. Low birth weight is also associated with a higher diabetes incidence. We aimed to examine to what extent the evolution of body shape, from childhood to adulthood, is related to incident diabetes in late adulthood. RESEARCH DESIGN AND METHODS: Etude Epidemiologique de Femmes de la Mutuelle Générale de l'Education Nationale (E3N) is a cohort study of French women born in 1925–1950 and followed by questionnaire every 2 years. At baseline, in 1990, women were asked to report their current weight, height, and body silhouette at various ages. Birth weight was recorded in 2002. Cases of diabetes were self-reported or obtained by drug reimbursement record linkage and further validated. RESULTS: Of the 91,453 women who were nondiabetic at baseline, 2,534 developed diabetes over the 15 years of follow-up. Birth weight and body silhouette at 8 years, at menarche, and in young adulthood (20–25 years) were inversely associated with the risk of diabetes, independently of adult BMI during follow-up (all P(trend) < 0.001). In mid-adulthood (35–40 years), the association was reversed, with an increase in risk related to a larger body silhouette. An increase in body silhouette from childhood to mid-adulthood amplified the risk of diabetes. CONCLUSIONS: Low birth weight and thinness until young adulthood may increase the risk of diabetes, independently of adult BMI during follow-up. Young women who were lean children should be especially warned against weight gain.